2015
DOI: 10.1017/s0021932015000073
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Mistimed and Unwanted Pregnancies Among Nepali Women

Abstract: Summary. This paper assesses the factors influencing mistimed and unwanted pregnancies in Nepal separately using data from the 2011 Nepal Demographic and Health Survey. Women who had given birth within the five years before the survey were interviewed about the intendedness of their last pregnancy. The data were analysed with a chi-squared test, followed by multiple logistic regression analysis. Among the total 5391 participants, 11.29% and 13.13% reported their last pregnancy as mistimed and unwanted respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
15
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
8
15
8
1
Order By: Relevance
“…Nevertheless, unlike other studies [16][17][18], it was not a determining factor in quality of life. Additionally, contrary to the results of other studies [19,20], the results of the present study demonstrated that economic status; number of pregnancies, and age…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, unlike other studies [16][17][18], it was not a determining factor in quality of life. Additionally, contrary to the results of other studies [19,20], the results of the present study demonstrated that economic status; number of pregnancies, and age…”
Section: Discussioncontrasting
confidence: 99%
“…Women's participation in households decision making has statistically significant correlation with the occurrence of unintended pregnancy. In-line with the previous study which stated that there was a statistically significant correlation between women's participation in households decision making with the occurrence of unintended pregnancy [17,18].…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, unlike other studies [16][17][18], it was not a determining factor in quality of life. Additionally, contrary to the results of other studies [19,20], the results of the present study demonstrated that economic status; number of pregnancies, and age were not related to planning for pregnancy.…”
Section: Discussioncontrasting
confidence: 99%